Five-year outcomes comparing percutaneous coronary intervention with drug-eluting stents versus coronary artery bypass grafting in patients with left main coronary artery disease: A systematic review and meta-analysis. (September 2020) - Zhang, Jian; Jiang, Tangxing; Hou, Yaping; Chen, Fengying; Yang, Kehui; Sang, Wentao; Wu, Hongzhi; Ma, Yanyan; Xu, Feng; Chen, Yuguo
Abstract: Background and aims: In patients with left main coronary artery disease (LMCAD), long-term outcomes after percutaneous coronary intervention (PCI) with drug-eluting stents (DES) compared with coronary artery bypass grafting (CABG) remain controversial. We conducted a meta-analysis to compare the efficacy and safety of PCI with DES and CABG in LMCAD patients. Methods: We comprehensively searched in Web of Science, EMBASE, PubMed, and Cochrane databases for eligible randomised controlled trials (RCTs) comparing the 5-year clinical outcomes between PCI with DES and CABG in LMCAD patients. Random-effect models were applied to analyse risk ratios (RRs) and hazard ratios (HRs) across studies, and I 2 to assess heterogeneity. Results: We screened 4 RCTs including 4394 patients distributed randomly into PCI (n = 2197) and CABG (n = 2197) groups. In comparison to CABG, PCI showed non-inferiority concerning a composite of death, myocardial infarction, and stroke (HR 1.22, 95% confident interval [CI] 0.84–1.75), death (HR 1.06, 95% CI 0.81–1.40) and stroke (HR 0.80, 95% CI 0.42–1.53). Regarding major adverse cardiac or cerebrovascular events (MACCE) rate, both strategies show clinical equipoise in patients with a low-to-intermediate Synergy Between PCI with TAXUS and Cardiac Surgery (SYNTAX) score (HR 1.20, 95% CI 0.85–1.70), while CABG had an advantage over PCI in those with a high SYNTAX score (HR 1.64, 95% CI 1.20–2.24). Conclusions: CABG showed advantage over PCI with DES for LMCAD patients in MACCE. PCI and CABG showed equivalent 5-year clinical risk of a composite of all-cause mortality, myocardial infarction, and stroke, but the former had higher risk of repeat revascularization. Graphical abstract: Image 1 Highlights: Long-term outcomes after percutaneous coronary intervention (PCI) with drug-eluting stents (DES) compared with coronary artery bypass grafting (CABG) remain controversial in left main coronary artery disease (LMCAD). CABG showed advantage over PCI with DES for LMCAD patients in major adverse cardiac or cerebrovascular events (MACCE). Both showed equivalent 5-year risk of composite of all-cause mortality, myocardial infarction, and stroke.